2017
DOI: 10.13168/cs.2017.0045
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Chloride Ingress in Steel Fibre Reinforced Concrete Under Bending Load

Abstract: Chloride induced corrosion is an important reason for the deterioration of reinforced

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…Moreover, D cr in FRC was one third smaller than that in PL. This relationship is close to the results reported in Wang et al (2018). The obtained D cr was adopted in the case study to calculate the corrosion initiation time in the cracked region.…”
Section: Chloride Diffusion In Cracked Concretesupporting
confidence: 85%
See 1 more Smart Citation
“…Moreover, D cr in FRC was one third smaller than that in PL. This relationship is close to the results reported in Wang et al (2018). The obtained D cr was adopted in the case study to calculate the corrosion initiation time in the cracked region.…”
Section: Chloride Diffusion In Cracked Concretesupporting
confidence: 85%
“…A recent investigation found the chloride diffusion coefficient to be reduced by 30-38% in steel fibre reinforced concrete beams compared to plain concrete ones, when the maximum bending stress in each specimen type was half the ultimate strength (Wang, Sun, Guo, Gu, & Zong, 2018). Other studies have also shown that adding fibres may significantly reduce corrosion-induced cover cracking, prevent cover spalling (Chen & Yang, 2019;Sadrinejad, Ranjbar, & Madandoust, 2018) and improve the residual post-peak bond capacity of corroded specimens (Berrocal, Fernandez, Lundgren, & L€ ofgren, 2017), as compared to reinforced mortar or concrete specimens without fibres.…”
Section: Introductionmentioning
confidence: 98%
“…This section discusses the existing models that deal with FRC especially in the area of corrosion. In a study by Wang et al [ 128 ], time to corrosion initiation of FRC was evaluated using Fick’s second law as shown in Figure 8 . The authors note that, although Fick’s second law is not able to physically represent the variety of mechanisms that lead to chloride ingress in concrete (e.g., capillary suction, wick action, wetting and drying cycles, etc.…”
Section: Remaining Service Life Of Frc Infrastructuresmentioning
confidence: 99%
“…The loading device is demonstrated in Figure 1. The same type of loading device has been adopted in several studies relating to the durability of flexural loaded concrete specimens [23,24]. The applied load was set to be 50 % of the ultimate flexural load of the UHPCs in this study.…”
Section: The Loading Strategymentioning
confidence: 99%